2021
DOI: 10.3390/jcm10102119
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Respiratory Function Test Three Months after Hospitalisation for COVID-19 Pneumonia: Value of Determining Nitric Oxide Diffusion

Abstract: Three to four months after hospitalisation for COVID-19 pneumonia, the most frequently described alteration in respiratory function tests (RFTs) is decreased carbon monoxide transfer capacity (DLCO). Methods: This is a prospective cohort study that included patients hospitalised because of SARS-CoV-2 pneumonia, three months after their discharge. A clinical evaluation, analytical parameters, chest X-ray, six-minute walk test, spirometry and DLCO–DLNO analysis were performed. Demographic variables, comorbiditie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 34 publications
0
25
3
1
Order By: Relevance
“…One recent study reported decreased total NO, nitrite and SNO in COVID-19 patients in hospital [ 36 ]. Another study in Spain showed that nitric oxide diffusion was reduced in around 40% patients discharged from hospital, via respiratory function tests with a MasterScreen PFT equipment [ 37 ]. To date, the levels of NO in blood among patients discharged from hospitals, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…One recent study reported decreased total NO, nitrite and SNO in COVID-19 patients in hospital [ 36 ]. Another study in Spain showed that nitric oxide diffusion was reduced in around 40% patients discharged from hospital, via respiratory function tests with a MasterScreen PFT equipment [ 37 ]. To date, the levels of NO in blood among patients discharged from hospitals, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In systemic endothelial dysfunction, the deficiency of the synthase-dependent pathway of NO generation can be corrected by its exogenous supplementation. Recent studies reported a decreased total NO and its metabolites in hospitalized COVID-19 patients, as well as a decreased nitric oxide diffusion in around 40% of patients discharged from the hospital [ 154 , 155 ]. Other authors claim that reduced concentrations of NO metabolites may be potential biomarkers of long-term poor or irreversible outcomes after a SARS-CoV-2 infection and might serve as a predictor to track the health status of recovered COVID-19 patients [ 156 ].…”
Section: Special Consideration Of Safety Ino In Covid-19mentioning
confidence: 99%
“…It has been shown that an increase in the concentration of fractional exhaled nitric oxide (FENO) indicated some diseases of the respiratory tract, such as asthma [ 7 , 8 , 12 , 13 ], allergy [ 9 , 14 , 15 ] and chronic cough [ 10 , 16 ]. Moreover, in connection with the COVID-19 pandemics, scientists have begun to publish works in which the analysis of the nitric oxide concentration could be useful for the diagnostics of coronavirus disease [ 17 , 18 ]. Several sensor devices have already been produced for the detection of FENO [ 19 ].…”
Section: Introductionmentioning
confidence: 99%